2017
DOI: 10.17586/2220-8054-2017-8-3-365-370
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional light bullets in Fermi liquid in the presence of magnetic field and AdS/CFT correspondence

Abstract: We consider the evolution of a light bullet in a fermi-liquid while considering the presence of a magnetic field. The energy spectrum for the Fermi liquid was calculated in the framework of AdS/CFT correspondence. The influence of a magnetic field's amplitude and its period on light bullet evolution was obtained. The stable character of the light bullet propagation in the Fermi liquid in the presence of a magnetic field was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Numerical calculations have shown that in the 2D case, stable nonlinear waves can occur and light pulses are localized in two directions, similar to "light bullets". When a "bullet" propagates in the Fermi fluid, its propagation in the horizontal direction is rather weak, while the energy is mainly concentrated in the central region of the pulse [38].…”
Section: Power Laws Of Dispersionmentioning
confidence: 99%
“…Numerical calculations have shown that in the 2D case, stable nonlinear waves can occur and light pulses are localized in two directions, similar to "light bullets". When a "bullet" propagates in the Fermi fluid, its propagation in the horizontal direction is rather weak, while the energy is mainly concentrated in the central region of the pulse [38].…”
Section: Power Laws Of Dispersionmentioning
confidence: 99%